Factors Affecting The Measurement of Intermediation Margin in Islamic Banks in Indonesia - Ira Novianty; Setiawan Setiawan; Rika Lisnawati (Jurnal ASET (Akuntansi Riset), 2023)
Main Purpose - The purpose of this study is to empirically assess the main factors that affect the bank margin of Islamic operations in Indonesia.Method - Hypothesis testing and data analysis used the Structural Equation Model - Partial Least Square (SEM-PLS. The research sample was conducted on 10 Islamic banks that have a dual banking system in Indonesia.Main Findings - The results of the study proved that the Capital Adequacy Ratio (CAR) had a positive and significant effect on the Net Intermediation Margin (NIM) and the size of the bank had a positive and significant effect on the Net Intermediation Margin (NIM). Meanwhile, Non-Performing Financing (NPF) and Operating Expenses of Operating Income (BOPO) had no effect on the net intermediation margin (NIM) in Islamic Banks.Theory and Practical Implications - The significant impact of the CAR and the size of the bank showed that there was an analysis of capital policy and product diversification on the bank. The high level of margin in Islamic banks can be an obstacle for Islamic banks to pursue the development process, therefore, there is a need for improvement in terms of liability, asset side, and operational side of the Bank in order to reduce NIM in Sharia Banks. Novelty - This research used BI rate and inflation as control variables in contrast to other studies that included BI Rate and inflation as independent variables.